Literasi Keuangan pada UMKM (Studi Pemetaan Sistematis dan Analisis Co-Authorship pada Basis Data Scopus) - Yogi Sugiarto Maulana; Erna Maulina; Nenden Kostini; Tetty Herawati (Universitas Winaya Mukti, 2021)
Financial literacy has been widely discussed in various countries with a wide range of subject areas, focuses, and loci. The purpose of this paper is to map the trends of scientific publications and map the network of authors on financial literacy, especially in the MSME sector. We have developed bibliometric analysis through VOSviewer software, supplemented by literature reviews. A total of 126 articles were obtained from Scopus related to the topics